Identification and pathogenic potentiality of fungi associated with Houttuynia cordata thunb. - Azad, Rumana; Shamsi, Shamim (Dhaka University Journal of Biological Sciences, 2011)
A total of 17 species of fungi representing 11 genera were found to be associated with Houttuynia cordata Thunb. The isolated fungi were Aspergillus flavus Link, Aspergillus niger Van Tiegh., Cercospora houtttuyniicola Goh et Hsieh, Colletotrichum coffeanum Noack, Colletotrichum dematium (Pers. Ex Fr.) Grove, Colletotrichum gloeosporioides (Penz.) Sacc., Curvularia brachyspora Boedijn., Curvularia fallax Boedijn., Curvularia pallescens Boedijn., Fusarium sp., Nigrospora sacchari (Speg.) Mason., Penicillium sp., Pestalotiopsis spp., Syncephalastrum sp., Trichoderma viride Pers. Ex Fries. and a member of Zygomycetes. Cercospora houtttuyniicola is a new record for Bangladesh. All the isolated fungi were tested for pathogenicity. Key words: Fungi; Association; Houttuynia cordata; Pathogenic potentiality DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8973 DUJBS 2011; 20(2): 131-138